2016
DOI: 10.1186/s40677-016-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long duration rainstorm on stability of Red-clay slopes

Abstract: Background: Slope stability issue in red clay slopes during rainfall is one among the serious geoenvironmental disasters in China. In order to investigate the effect of long duration rainstorm on red-clay slopes, studies were conducted using Geostudio 2012. Five different rainfall-durations were applied to the slope and the results of coupled and uncoupled calculation modes were compared. Results and Conclusions: Results show that pore water pressure increased due to the dissipation of matric suctions and rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…It has been reported that in the last decade, urban floods have impacted most parts of the world including the USA, Europe, Asia, and Africa [6][7][8][9][10][11][12]. Flooding occurs in the least developed nations as well as in the most developed countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in the last decade, urban floods have impacted most parts of the world including the USA, Europe, Asia, and Africa [6][7][8][9][10][11][12]. Flooding occurs in the least developed nations as well as in the most developed countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…When the rainwater in ltrates into soil, the suction decreases and pore water pressure rises. As the result, the movement to down slope will cause slope instability (Gofar and Lee 2008; Xue et al 2016). In this case, rainfall on 18 and 27 July does not affect the pore water pressure as shown in Fig.…”
Section: Input Parameters and Materials Modelmentioning
confidence: 97%
“…When the water level drops in the saturated soil, a decline curve is formed because of water lag time, and excess pore pressure can lead to the bank destruction [Alfatlawi et al 2020]. A slope stability decrease is noted also in the works by [Xue et al 2016, Acharya et al 2016, Duong et al 2019, Liu et al 2015] that is related to the penetration of water into unsaturated soil during the rain. Water penetration into the soil depends on the geological structure of floodplain banks.…”
Section: Introductionmentioning
confidence: 96%